The Need Analysis of the Electronic Students Worksheet of Observation Report Text Based on Merdeka Curriculum in Senior High School - Hadi Wijaya; Mulyadi Eko Purnomo; Zahra Alwi (STAI Hubbulwathan Duri, 2023)
The Curriculum of Merdeka is characterised by a novel paradigm centred around the concept of independence. It enables students and educators to cultivate an autonomous mindset. The curriculum implemented by Merdeka fosters an environment that promotes active and creative learning. Furthermore, it is imperative that the curriculum of Merdeka incorporates learning activities for each topic that align with the desired results and profile of Students of Pancasila. This study aimed to conduct a needs analysis of the Curriculum of Merdeka-based electronic students worksheet (E-LKPD) for tenth-grade students at a public senior high school in Palembang. The objective of this study was to enhance the attributes and requirements of students in class X throughout their study of the Indonesian language in senior high school. The research employed a mixed methods design, incorporating both qualitative and classroom action research methodologies. The study results indicated that a significant proportion of students, specifically 67.2%, expressed a need for interactive and digital teaching materials. These materials would imitate items observed through the utilisation of E-LKPD, which has been enhanced with interactive features. According to the findings, a significant proportion of students, namely 43%, shown a lack of proficiency in composing observation report texts. Additionally, all teachers expressed a need for interactive learning resources to assess the efficacy of enhancing student learning outcomes in the field of Bahasa Indonesia.